Management and complications of tubo-ovarian abscesses: a brief literature review - Akıncı, Güzide Ece; Bornaun, Teymur; Güven, Hamit Zafer (The European Research Journal, 2024)
Tubo-ovarian abscesses (TOAs) are identified as a severe and complex form of inflammatory disorder, marking an advanced progression of pelvic inflammatory disease (PID), mainly resulting from the escalation of polymicrobial infections within the female genital tract. This literature review is dedicated to elucidating the contemporary management strategies and associated complications of TOAs, amalgamating the current scholarly discourse while spotlighting the emerging therapeutic trends. The inherent complexity of TOAs, manifesting through a broad array of clinical presentations from mild symptoms to acute pelvic discomfort and fever, necessitates a comprehensive, multidisciplinary approach to achieve effective management. Traditional management has predominantly focused on antibiotic therapy, the cornerstone of initial treatment modalities. Nonetheless, this review expands on the increasing acknowledgment of minimally invasive surgical interventions, like ultrasound-guided drainage, especially in scenarios where medical therapy falters or in the presence of sizable abscesses, underscoring scenarios where antibiotic treatment may be insufficient. The discourse further explores the pivotal decision-making concerning surgical interventions, juxtaposing the benefits of abscess resolution against potential risks and complications, such as damage to adjacent structures and implications for future fertility. The review emphasizes the criticality of addressing PID’s risk factors and root causes to avert TOA development. It also ventures into the ramifications of the emergence of antibiotic-resistant bacterial strains for empirical antibiotic therapy selection, highlighting the imperative for continuous research and the adaptation of therapeutic guidelines. The complications associated with TOAs, including sepsis, infertility, and chronic pelvic pain, are meticulously examined to underscore the potential for significant long-term morbidity. Advocating for prompt diagnosis and encompassing management strategies to curtail these adverse outcomes, the review ultimately calls for intensified, quality research to refine TOA management further, particularly against the backdrop of evolving microbial resistance and the advancements in minimally invasive surgical technologies.